How urban sprawl influences eco-environmental quality: Empirical research in China by using the Spatial Durbin model. (November 2021) - Chen, Danling; Lu, Xinhai; Hu, Wenbo; Zhang, Chaozheng; Lin, Yaoben
Highlights: Urban sprawl (UBS) index and eco-environmental quality (EEQ) index are built. The impact of UBS on EEQ is investigated theoretically and empirically. Spatial Durbin model is used, taking China's provincial panel data from 2003 to 2018. Population sprawl, socio-economic sprawl, transportation sprawl, and land use sprawl explain EEQ change. It is necessary to incorporate the spatial effect into urban development planning. Abstract: Rapid urban sprawl in China has caused serious eco-environmental changes, and thus attracted significant attention of the international academic circles. However, the mechanism of influence of urban sprawl on eco-environmental quality has not been addressed adequately. The main objective of this study was to fill this gap by theoretically and empirically studying how urban sprawl influences eco-environmental quality, based on the Spatial Durbin model and on a panel data covering 30 provinces of mainland China during the period 2003–2018. The results show that China's urban sprawl has significantly decreased the eco-environmental quality under both geographical and economic weight matrices. Moreover, the spillover effect played an essential role in investigating the influence of urban sprawl on eco-environmental quality. From the perspective of regional differences, the direct accumulation effect and the spatial spillover effect involved in the impact of urban sprawl on eco-environmental quality varied across the central, western, and northeast regions. The results of decomposition of urban sprawl into its component parts indicate that population sprawl, socio-economic sprawl, transportation sprawl, and land use sprawl can explain the change of eco-environmental quality in China to varying degrees. During the study period, land use sprawl exhibited the greatest effect on eco-environmental quality, followed by socio-economic sprawl, population sprawl, and transportation sprawl. The government should actively coordinate the development of different types of urban sprawl, thus increasing eco-environmental quality across different regions.